2013
DOI: 10.1088/0004-637x/778/2/139
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spine Loops and the Nature of a Late-Phase Solar Flare

Abstract: The fan-spine magnetic topology is believed to be responsible for many curious features in solar explosive events. A spine field line links distinct flux domains, but direct observation of such feature has been rare. Here we report a unique event observed by the Solar Dynamic Observatory where a set of hot coronal loops (over 10 MK) connected to a quasi-circular chromospheric ribbon at one end and a remote brightening at the other. Magnetic field extrapolation suggests these loops are partly tracer of the evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
231
5
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(265 citation statements)
references
References 97 publications
25
231
5
4
Order By: Relevance
“…Using our rough proxy for emission, we showed that these cooling threads may be observable as criss-crossing thread-like features in the connecting coronal loop. Sun et al (2013) described a large coronal jet similar in morphology to our = L N 2.40 case. They observed crisscrossing threads within the loop and a two-phase emission suggestive of shuffling reconnection and possible heating within the cooling loop, supporting the picture we have deduced from our simulations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Using our rough proxy for emission, we showed that these cooling threads may be observable as criss-crossing thread-like features in the connecting coronal loop. Sun et al (2013) described a large coronal jet similar in morphology to our = L N 2.40 case. They observed crisscrossing threads within the loop and a two-phase emission suggestive of shuffling reconnection and possible heating within the cooling loop, supporting the picture we have deduced from our simulations.…”
Section: Discussionsupporting
confidence: 79%
“…It is expected that jets can occur across the full range of L/N. Reported values range from 2.5 to 4 in large-scale jets (e.g., Sun et al 2013;Cheung et al 2015) to 5 and higher in small-scale jets (e.g., Zhang & Ji 2013;Zhang et al 2016). Over the parameter range studied in WD16, the threshold for triggering the kink instability that led to the jet, as well as the subsequent jet dynamics, were found to depend strongly on the ratio L/N.…”
Section: Jet Modelmentioning
confidence: 99%
“…In an embedded bipolar magnetic configuration, a spine links the magnetic null point to infinity (Fletcher et al 2001;Pariat et al 2010;Liu et al 2011;Jiang et al 2013) or to a remote place on the solar surface (Filippov 1999;Masson et al 2009;Wang & Liu 2012;Sun et al 2013). In the latter case, the released thermal energy and accelerated particles during reconnection would be transferred along the magnetic spine to heat the chromosphere and produce brightening at the other footpoint of spine, which has been discovered in flares (Biesecker & Thompson 2000;Wang et al 2001;Moon et al 2002;Brosius & Holman 2007;Su et al 2013).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…However, in events with complicated magnetic topology, SFRs are initiated. Similar to the flares with the late phase, 10 of the 11 SFRs may result from largescale secondary magnetic reconnection triggered by the initial magnetic reconnection in the main flare regions (Woods et al 2011;Liu et al 2013;Sun et al 2013). Another possibility is that the returning filament material interacts with the solar atmosphere and generates the observed SFRs.…”
Section: Type Ii: Sfr Appearing Subsequently To the Frsmentioning
confidence: 98%
“…The EUV emission of flares exhibits a second peak separated from the first peak by tens of minutes to hours (Woods et al 2011;Liu et al 2013;Sun et al 2013). The second peak originates from the cooling of the higher and larger-scale coronal loops.…”
Section: Introductionmentioning
confidence: 99%